2011
DOI: 10.1007/s00467-011-1815-z
|View full text |Cite
|
Sign up to set email alerts
|

Karyomegalic-like nephropathy, Ewing’s sarcoma and ifosfamide therapy

Abstract: Karyomegalic interstitial nephropathy has been reported as a rare interstitial nephritis in adult patients. Histology shows atypical epithelial cells and large abnormal hyperchromatic nuclei with irregular outlines. We report 3 adolescent patients who all recovered from their initial treatment for Ewing's sarcoma but developed a tubulopathy attributed to ifosfamide therapy. Renal impairment resulted in biopsy, which showed features of karyomegalic nephropathy in all 3. One patient has progressed to haemodialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
(13 reference statements)
3
21
0
Order By: Relevance
“…Most of reports show the chronic tubulointerstitial damage, although segmental glomerular sclerosis was also reported [8], which were also found in the present case. We also found the lesion typical of karyomegalic interstitial nephritis, which was also recently reported in ifosfamideinduced late-onset nephrotoxicity [9]. The authors presented three cases that were treated with ifosfamide, but without cisplatin.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Most of reports show the chronic tubulointerstitial damage, although segmental glomerular sclerosis was also reported [8], which were also found in the present case. We also found the lesion typical of karyomegalic interstitial nephritis, which was also recently reported in ifosfamideinduced late-onset nephrotoxicity [9]. The authors presented three cases that were treated with ifosfamide, but without cisplatin.…”
Section: Discussionsupporting
confidence: 79%
“…There are several reports of the finding of renal biopsy for ifosfamide-induced late nephropathy [3,[8][9][10][11][12]. Most of reports show the chronic tubulointerstitial damage, although segmental glomerular sclerosis was also reported [8], which were also found in the present case.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a report by Hassan et al [5], high concentration of ochratoxin was found in the blood of affected siblings. McCulloch et al [6], reported KIN in three adolescent patients treated with ifosfamide for Ewings sarcoma. Tomokazu Matsuura et al reported a case of a 15-year-old boy presented with progressive nephrotoxicity 3 years after systemic chemotherapy with ifosfamide and cisplatin for the treatment of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…[6] All patients progressed to renal failure. A familial clustering is known and frequency of human leukocyte antigen (HLA)-A9 and HLA-B35 haplotypes suggest the possibility of genetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%